Evaluation of perceived family burden, care burden and quality of life of caregivers during the pandemic period - Yildiz, Sevler; Kazgan, Asli; Kurt, Osman; Korkmaz, Sevda (Bayrakol Medical Publisher, 2021)
Aim: In this study, we aimed to evaluate the perceived family burden, caregiving burden and the quality of life of people who have to spend most of their time at home with their patients during the pandemic period and who provide home care for patients diagnosed with psychotic disorder. Material and Methods: The study included caregivers of 91 patients with a diagnosis of psychotic who admitted to the psychiatry outpatient clinic during the pandemic period and met the study criteria. All participants were applied the World Health Organization Quality of Life Form (WHOQOL-BREF-TR), Perceived family burden scale (PFBS), and the Zarit Caregiver Burden Scale (ZBS). Results: Participants' mean PFBS score was 65.6 +/- 19.1 and their ZBS mean score was 56.2 +/- 14.8. A positive correlation was found between PFBS score and ZBS score (p=0,00, r=0,763). Also, a significant negative correlation was found between PFBS score and WHOQOL-BREF-TR scale sub-scales and the ZBS score and the WHOQOL-BREF-TR scale sub-scales. Discussion: The pandemic period negatively affected caregivers of patients diagnosed with psychosis.
Keywords: COVID-19; Psychosis; Caregiving burden; Perceived burden; Quality of life